Relationship between Type 2 Diabetes Mellitus and cognitive impairment in Peru’s Navy Medical Center’s older adult patients between 2010 to 2015. - Zapata-Tragodara, Daniela (2020)
Diabetes Mellitus (DM), a metabolic disorder characterized by chronic hyperglycemia, can be due to a defect in insulin secretion, a defect in its action, or both. Neurocognitive disorders or "organic mental disorders" present three categories: delirium, minor (or mild) impairment, and major neurocognitive disorder or dementia. These are two very prevalent conditions; several epidemiological studies have shown some characteristics common to both of them. Objective: To determine the relationship between Type 2 DM and neurocognitive disorders in an older adult population. Material and Methods: Analytical, retrospective, and secondary database study of investigations carried out between 2010 and 2015 in a population of 1,896 older adults, attended in the Geriatric service of the Naval Medical Center, the main hospital of the Peruvian Navy. Results: A higher frequency of male patients (58.4%) was found, the most frequent age group (46.4%) was 71-80 years, and the frequency of DM was 16.86%. In the bivariate analysis, 30.67% of participants with neurocognitive disorders had a history of DM, with statistically significant differences; in addition, variables such as age, sex, education, social support, polypharmacy, sedentary lifestyle and 7.03 average of glycosylated hemoglobin were also statistically significant. Conclusions: A relationship was found between DM and neurocognitive disorders. Being male seems to be a protective factor against cognitive decline. Hyperglycemia causes cognitive impairment, with glycosylated hemoglobin being a determinant test in the assessment of older diabetics with cognitive problems.